Odpowiedzi

2009-12-09T18:27:28+01:00
A) (2a+b)×c-(2ac-bc+1)=2ac+bc-2ac+bc-1=2bc-1
b)5(x-z)+2(z-x)=5x-5z+2z-2x=3x-3z
c)2x²(x-5)-3x(x²-3x+5)=2x³-10x²-3x³+9x²-15x=-x³+x²-15x
d)6(a²+b+⅓)-6(a²-½)-3(b+⅓)=6a²+6b+2-6a²+3=6b+5
2009-12-09T18:29:57+01:00
A) 2ac+bc-2ac+bc+1=2bc+1
b)5x-5z+2z-2x=3x-3z
c)2x³-10x²-3x³+9x²-15x=-x³-x²-15x
d) 6a²+6b+2-6a²-3-3b+1= 3b
Najlepsza Odpowiedź!
2009-12-09T18:31:07+01:00
Zapisz w postaci sumy albebraicznej:

a) (2a+b)×c-(2ac-bc+1)=2ac+bc-2ac+bc-1=
2bc-1

b)5(x-z)+2(z-x)=5x-5z+2z-2x=
3x-3z= 3(x-z)

c)2x²(x-5)-3x(x²-3x+5)=2x³-10x²-3x³+9x²-15x=
-x³-x²-15x= -x(x²+x+15)

d)6(a²+b+⅓)-6(a²-½)-3(b+⅓) =6a²+6b+2-6a²+3-3b-1=
3b+4